Photographic Presidents Making History from Daguerreotype to Digital - Finnegan, Cara A. (University of Illinois Press, 2021)
Defining the Chief Executive via flash powder and selfie sticks Lincoln's somber portraits. Lyndon Johnson's swearing in. George W. Bush's reaction to learning about the 9/11 attacks. Photography plays an indelible role in how we remember and define American presidents. Throughout history, presidents have actively participated in all aspects of photography, not only by sitting for photos but by taking and consuming them. Cara A. Finnegan ventures from a newly-discovered daguerreotype of John Quincy Adams to Barack Obama's selfies to tell the stories of how presidents have participated in the medium's transformative moments. As she shows, technological developments not only changed photography, but introduced new visual values that influence how we judge an image. At the same time, presidential photographs-as representations of leaders who symbolized the nation-sparked public debate on these values and their implications. An original journey through political history, Photographic Presidents reveals the intertwined evolution of an American institution and a medium that continues to define it.